2016
DOI: 10.3390/ijms17071129
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Lipogenesis Inhibits Adiponectin Production in Human Dermal Fibroblasts while Exogenous Adiponectin Administration Prevents against UVA-Induced Dermal Matrix Degradation in Human Skin

Abstract: Adiponectin is one of the most abundant adipokines from the subcutaneous fat, and regulates multiple activities through endocrine, paracrine, or autocrine mechanisms. However, its expression in adipogenic induced fibroblasts, and the potential role in photoaging has not been determined. Here, human dermal fibroblasts, Hs68, were presented as a cell model of dermal lipogenesis through stimulation of adipogenic differentiation medium (ADM). Similar to other studies in murine pre-adipocyte models (i.e., 3T3-L1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 40 publications
1
17
0
1
Order By: Relevance
“…However, in skin wound healing, the role of lipogenesis in dermal fibroblasts were under investigated and the mechanisms has yet to be defined. Our previous study confirmed that adipogenic differentiation medium (ADM) can stimulate the differentiation of Hs68 human dermal fibroblasts to adipocyte-like cells through the lipid accumulation and mRNA expressions of PPAR-γ, LPL and FABP4 ( Fang et al, 2016 ). In the present study, we aim to further investigate the impact of lipogenesis on the inflammation responses and ECM formation in Hs68 fibroblasts.…”
Section: Introductionsupporting
confidence: 66%
“…However, in skin wound healing, the role of lipogenesis in dermal fibroblasts were under investigated and the mechanisms has yet to be defined. Our previous study confirmed that adipogenic differentiation medium (ADM) can stimulate the differentiation of Hs68 human dermal fibroblasts to adipocyte-like cells through the lipid accumulation and mRNA expressions of PPAR-γ, LPL and FABP4 ( Fang et al, 2016 ). In the present study, we aim to further investigate the impact of lipogenesis on the inflammation responses and ECM formation in Hs68 fibroblasts.…”
Section: Introductionsupporting
confidence: 66%
“…The dermis is composed of fibrous structural collagen-rich extracellular matrix (ECM) which is essentially responsible for the skin's tensile strength and mechanical properties, together with elastin and hyaluronic acid. 1,2) Upon exposure to solar UV, especially UVB, degradation of ECM is being processed through activation of matrix metalloproteinases (MMPs) with decreased pro-collagen synthesis, resulting in wrinkle formation and sagging skin (skin photoaging). 3) A great number of plant extracts and phytochemicals including polyphenols (flavonoids and non-flavonoids) and non-phenolic derivatives possess anti-oxidant and anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…8,10 UVA-induced activation of EGFR has been reported by previous in vivo and in vitro studies 13,17 . Fang et al 35 found that 2.808 J/cm 2 UVA irradiation leads to increases in EGFR expression in Hs68 fibroblast cells.…”
Section: Discussionmentioning
confidence: 99%
“…The level of collagen in the normal skin is maintained by the balance between synthesis in dermal fibroblasts and enzymatic degradation by MMPs and tissue inhibitors of metalloproteinases (TIMPs) which can be induced by UV irradiation. 8,10,35 MMPs are a family of zinc-and calcium-dependent endoproteinases, which are capable of degrading collagen, elastin, and other components of the ECM of the skin. It has been reported that MMP-1, interstitial collagenase, and MMP-3, stromelysin-1, are both responsible for the degradation of dermal collagen and their activities are regulated by their interactions with TIMPs.…”
Section: Introductionmentioning
confidence: 99%